Perceptions and experiences of exercise participation among persons with amyotrophic lateral sclerosis: A qualitative study. Issue 3 (4th May 2023) - Man, Kristiann E.; Sawula, Laura; Gurd, Brendon J.; Taylor, Sean; Allen, Matti D.; Tomasone, Jennifer R.
ABSTRACT: Our work sought to understand perceptions and experiences of exercise participation from the perspectives of persons living with amyotrophic lateral sclerosis (ALS). Data were collected through semi-structured interviews with seven participants with ALS. Using an interpretivist approach, we engaged in reflexive thematic analysis. Two overarching themes were identified: 1) negotiating exercise participation is complex and 2) the environmental conditions influencing access to exercise. Within the first overarching theme, three key subthemes were found: i) the psycho-emotional experience of ALS, ii) reconceptualising exercise as medicine, and iii) antecedents to exercise participation. Further, three additional subthemes arose within the overarching theme of environmental conditions influencing access to exercise: i) location and access matter, ii) the multifaceted nature of care, and iii) aspects of quality exercise delivery. Findings offer novel insights on the complexity of navigating exercise participation for persons with ALS. Although exercise may be beneficial for individuals with ALS, healthcare professionals, researchers, and policymakers need to consider adopting a cautious and individualised approach when contemplating exercise participation for persons with ALS.